2023
DOI: 10.1021/acs.orglett.3c00073
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Responsive Boron-Spiro-Centered π-Electronic Systems That Form Ion-Pairing Assemblies

Abstract: A variety of naphthalenediolates were orthogonally introduced to the boron unit of dipyrrolyldiketone boron complexes, exhibiting electronic properties that depended on the substituting positions of the naphthyl moieties. Combining the anion complexes with countercations resulted in the formation of ion-pairing assemblies with supporting stacking interactions of the naphthyl units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Maeda et al reported that a series of naphthalenediols can be orthogonally introduced to the boron unit of dipyrrolyl diketone boron complexes, which were generated in situ from dipyrrolyl diketones and BCl 3 (Scheme S8). The unique spiroborate structure gives rise to two kinds of π electronic systems that are perpendicular to each other. These boron complexes exhibited effective anion-binding behavior in the solution state and also formed diverse stacking assemblies.…”
Section: Tetracoordinate Boratesmentioning
confidence: 99%
“…Maeda et al reported that a series of naphthalenediols can be orthogonally introduced to the boron unit of dipyrrolyl diketone boron complexes, which were generated in situ from dipyrrolyl diketones and BCl 3 (Scheme S8). The unique spiroborate structure gives rise to two kinds of π electronic systems that are perpendicular to each other. These boron complexes exhibited effective anion-binding behavior in the solution state and also formed diverse stacking assemblies.…”
Section: Tetracoordinate Boratesmentioning
confidence: 99%
“…78 Furthermore, introducing naphthalenediolate units instead of two fluorine moieties at the boron unit affects the assembling modes. 79 In the assembly of the naphthalene-2,3-diolate boron complex as a 3 TATA + ion pair 3 TATA + - 43a ·Cl − , the stacked 3 TATA + dimer is sandwiched by the naphthyl unit of 43a ·Cl − . Conversely, in 3 TATA + - 43b ·Cl − , alternately stacked 3 TATA + and the receptor–Cl − complex unit in 43b ·Cl − are observed (Fig.…”
Section: π-Electronic Systems With Charge Introduced By Noncovalent I...mentioning
confidence: 99%